Tracer Study Analysis on Alumni Master of Management Study Program, Universitas Trisakti Indonesia - Risqiani, Renny; Nilasari, B. Medina; Leon, Farah Margaretha; Kurniawati (Archives of Business Research, 2025)
This study aims to determine the profile of alumni from the Master of Management Program at the Faculty of Economics and Business, Universitas Trisakti (MM FEB Usakti). The respondents for this study are alumni of the MM FEB Usakti program who graduated in 2022-2023. The type of research used is descriptive research with a quantitative approach. The data used is primary data collected through a survey by distributing questionnaires to the respondents. The data was analyzed using SPSS software. There were 245 graduates of the MM FEB Usakti, in 2022-2023, but only 200 respondents completed the tracer study questionnaire. The questionnaires were distributed directly to alumni or alumni contacts whose whereabouts were known. The research results show that 97% of MM FEB Usakti alumni already had jobs upon graduation, either by directly seeking employment or through information from friends. 50% of graduates work in their field of study. Alumni are assessed by employers as having expertise based on their field of study (professionalism) and good self-development, but they still need to improve their ability to use English as an international language. The results of this tracer study can be used as material for evaluation and improvement by the leadership of MM FEB Usakti in relation to graduate profiles and the skills that graduates must have, both soft skills and hard skills, in order to be competitive in the world of work.